EFFECTIVENESS OF PHENOMENON BASED LEARNING (PHENOBL) MODEL APPLICATION FOR IMPROVING STUDENT LEARNING RESULTS IN OPTICAL MATERIALS - Tesa Liantika Putri; Azizahwati Azizahwati; Nur Islami (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
The learning process of physics at school, the topics is sometime less relatedto the existing dailylife phenomenon.This condition causes low improvement of students' cognitive learning result. In this case, it was a necessary to apply a learning model to improve student learning result by applying phenomenon based learning model (PhenoBL). Quasi experiment in the form of nonequivalent control group design as the model of the research. The instrument to collect data used test of student cognitive at pretest and posttest, respectively. The Data was analyzed by descriptive and inferential analysis. The results of descriptive analysis show the average absorption rate of experiment class is 71.05% and control class is 63.33% which both classes are in a good category. In the paired sample t-test results stated an increasing of students cognitive learning outcomes from pretest to posttest. This can also be seen from the inferential analysis in that means there was a significant differences between experimental class and kontrol class. Thus, it can be concluded that the use of PhenoBL model can improve student learning outcomes of class XI MIPA SMA Negeri 5 Pekanbaru on optical material.